The global threat of antibiotic resistance: what can be done? - Christopher J Graham (Inishmore Laser Scientific Publishing Ltd, 2017)
In addition to treating bacterial infections, antibiotics guard against infections. Antibiotics make surgical operations possible, promote the survival of premature babies, and enable immunosuppression (e.g. cancer chemotherapy). With an ageing and increasingly overweight global population, chronic illnesses treated surgically (e.g. hip replacements) may become very hazardous without effective antibiotics. Due to antibiotic misuse and a lack of successful development of new antibiotics, antibiotic resistance is an increasing global threat. In this overview, I address the problem of the global threat of antibiotic resistance through the following sections: A brief history of antibiotics; What are antibiotics used for?; How does antibiotic resistance develop?; How does antibiotic resistance spread?; Why is resistance an increasing problem?; Why are there no new antibiotics?; How bad is the problem?; and What can we do?